Fumigation Toxicity of Essential Oil Monoterpenes to Callosobruchus maculatus (Coleoptera: Chrysomelidae: Bruchinae). (7th October 2014) - Ajayi, Olufunmilayo E.; Appel, Arthur G.; Fadamiro, Henry Y.
Abstract : The fumigant toxicity of eight essential oil components, 1-8-cineole, carvacrol, eugenol, (−)-menthone, (−)-linalool, S-(−)-limonene, (−)- β -pinene, and (+)- α -pinene, was tested against the cowpea weevil, Callosobruchus maculatus (Fabricius) (Coleoptera: Chrysomelidae), at 0.25–60  µ L/L air doses. 1-8-Cineole, carvacrol, and eugenol caused complete adult mortality at 10  µ L/L air 24 h after treatment. 1-8-Cineole and carvacrol were the most toxic with LD50 values of 0.24 and 0.6  µ L/L air at 24 h, respectively. (−)- β -Pinene and (+)- α -pinene were the least toxic with LD50 values of 31 and 31.4  µ L/L air at 24 h, respectively. Toxicity was negatively correlated with vapor pressure. 1-8-Cineole and carvacrol caused 100% oviposition deterrence at all doses tested. Eugenol and (−)-menthone completely inhibited adult emergence. S -(−)-Limonene, (−)- β -pinene, and (+)- α -pinene were not effective at preventing oviposition or adult emergence, suggesting that a lethal dose of the three oil components would be necessary to control C. maculatus infestations.